2018
DOI: 10.1177/1049909118768247
|View full text |Cite
|
Sign up to set email alerts
|

“Sacred Pause” in the ICU: Evaluation of a Ritual and Intervention to Lower Distress and Burnout

Abstract: Sacred pause brings closure, prevents cumulative grief and distress, builds resilience, promotes team effort, and improves professional satisfaction of ICU team. It may lower burnout syndrome in ICU, but further studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 42 publications
1
22
0
7
Order By: Relevance
“…In our study we did not name the moments of rituals as 'pauses'. However, like Kapoor et al (2018), we found that when nurses were performing rituals, these moments were also significant in themselves.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In our study we did not name the moments of rituals as 'pauses'. However, like Kapoor et al (2018), we found that when nurses were performing rituals, these moments were also significant in themselves.…”
Section: Discussionmentioning
confidence: 51%
“…The Pause permits nurses to feel present and composed, provides a moment for reflection, and is a method to honour a deceased patient. Kapoor et al (2018) performed a quantitative study demonstrating that the majority of ICU physicians and nurses participating in the study who practised a 'sacred pause' believed that the ritual brought closure and helped them overcome the feelings of disappointment, grief, distress and failure after the death of their patient in ICU. They also found that a majority agreed that the ritual had implanted a sense of team cohesion.…”
Section: Discussionmentioning
confidence: 99%
“…Por otra parte, narran que con el tiempo van generando estrategias individuales y grupales para superar la pérdida de los pacientes, como es el aceptar el apoyo dado por pares y sus propios familiares 12,14 . En cuanto a los pares, este apoyo se materializa en la posibilidad de compartir las vivencias de pérdida a través de conversaciones informales entre un grupo pequeño de funcionarios y/o la posibilidad de expresar libremente sus emociones en un ambiente protegido 15,17,18 . En el caso de su familia, Gálvez et al señala que es dentro de ésta donde los profesionales se sienten mayormente contenidos, al encontrar comprensión y apoyo emocional 14 .…”
Section: Discussionunclassified
“…Los profesionales de unidades de UCI pediátricos requieren que las muertes de sus pacientes sean reconocidas como pérdidas profesionales, para lo que se considera fundamental recibir el apoyo de sus compañeros, familiares y de la propia institución donde trabajan. A pesar que existen obstáculos que no les permiten despedirse y dar un cierre a la relación con los pacientes 15,16 , ellos consideran que se podrían desarrollar ritos que favorezcan la elaboración de procesos de cierre a través de una pausa corta de tiempo dentro de su rutina laboral, considerándolas como "pausas sagradas" 17 . A eso se suma, el crear instancias para poder conversar de su pesar y de las propias vivencias 13 , pudiendo mejorar las instancias de comunicación dentro de equipo, y favorecer la cohesión entre compañeros, elemento clave en este tipo de procesos 24 .…”
Section: Conclusiónunclassified
See 1 more Smart Citation